A comparative study on the machining characteristics on turning AISI 52100 alloy steel in dry and microlubrication condition. Issue 2 (15th March 2022) - Rajarajan, S.; Ramesh Kannan, C.; Dennison, Milon Selvam
ABSTRACT: This paper elucidates the outcome of machining factors specifically cutting velocity, feed rate and depth of cut on the machining characteristics such as surface roughness and tool-work interface temperature while turning cylindrical AISI 52100 steel alloy components in dry and microlubrication machining conditions. The experiments are designed based on the Taguchi's L25 (5 3 ) orthogonal array and conducted on an All Geared Lathe, simultaneously the tool-work interface temperature was observed using a K-type tool-work thermocouple and subsequently, a mathematical model was developed for the tool-work interface temperature values through regression analysis. The surface roughness of the turned steel alloy components is deliberated by means of a precise surface roughness apparatus. A prediction model in lieu of average surface roughness is created by means of nonlinear regression examination with the aid of MINITAB software. The most favourable machining settings are recognised by Taguchi's method and verified with a confirmation trial. The results revealed that machining under microlubrication condition exhibited lesser temperature at the tool-work interface and the quality of the machined components also exhibits lesser roughness when compared with components of dry machining condition.